2004
DOI: 10.1364/ol.29.002160
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-wave Rabi flopping: role of the carrier-envelope phase

Abstract: Recently, a dependence of Rabi f lopping on the carrier-envelope phase of the exciting laser pulses was predicted theoretically [Phys. Rev. Lett. 89, 127401 (2002)] for excitation of a thin semiconductor film with intense few-cycle pulses. Here, we report corresponding experiments on 50 -100-nm thin GaAs films excited with 5-fs pulses. We find a dependence on the carrier-envelope phase arising from the interference of sidebands from the fundamental or the third-harmonic Mollow triplet, respectively, with surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…The CEP controllability of electron dynamics in the case of resonant excitation, ω 0 ∼ E g , has so far mostly been studied in the context of carrier-wave Rabi flopping (CWRF) [14][15][16][17] , where the motion of charge carriers within bands was neglected, as well as in the context of perturbative ω + 2ω interference 18,19 , where a relatively weak field limits the scope of the intraband motion.…”
Section: Introductionmentioning
confidence: 99%
“…The CEP controllability of electron dynamics in the case of resonant excitation, ω 0 ∼ E g , has so far mostly been studied in the context of carrier-wave Rabi flopping (CWRF) [14][15][16][17] , where the motion of charge carriers within bands was neglected, as well as in the context of perturbative ω + 2ω interference 18,19 , where a relatively weak field limits the scope of the intraband motion.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the period of these CEP-dependent signals is 2π . This is different from the interference case in symmetric media [15,20,21], in which the CEP-dependent period is π . To illustrate the underlying physics, we calculate the dipole-induced emitted field spectra (Ê em (ω) ∝ FFT − ∂P x ∂t [44]) from the medium at the same propagation distance as in figure 1.…”
Section: Theoretical Modelmentioning
confidence: 75%
“…In the resonant interaction regime, the ionization can be ignored due to the lower laser intensity. However, the CEP-dependent signals can still be found in the transmitted spectra [15,[20][21][22]. Previous investigations in inversion-symmetric media have shown that these CEPdependent signals are originated from the interference effects between different harmonic components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another embodiment, the laser inducing the Rabi oscillation is self-modulated by nanosecond duration pulses generating sidebands in Na vapor at ± 3.5 meV 16,17 . Thin GaAs films 18,19 have been used recently to demonstrate Rabi shifting on the order of the carrier frequency in the optical regime using a carrier-envelope phase stabilized femtosecond pulse. We report here a Rabi shift on the order of 100 meV using a micro plasma driven by a picosecond laser pulse with large detuning from resonant states in the plasma atoms (' ~2% Z c ).…”
Section: Introductionmentioning
confidence: 99%